2019
DOI: 10.1021/acschemneuro.9b00081
|View full text |Cite
|
Sign up to set email alerts
|

Classics in Neuroimaging: Development of PET Tracers for Imaging Monoamine Oxidases

Abstract: In this Viewpoint, we highlight the history of positron emission tomography (PET) radiotracer development to quantify changes in monoamine oxidase (MAO)-A and -B enzyme expression or activity. MAO-A and MAO-B are critical for understanding monoaminergic pathways in psychiatric addiction disorders, and more recently in neurodegenerative disorders with MAO-B expression in astrogliosis. Unique radiochemical innovations have been shown for neuroimaging of MAOs including the clinical translation of irreversible pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 6 publications
0
39
0
Order By: Relevance
“… 7 , 8 Recent studies by an author of this article also demonstrated that the tau PET tracers also target the same binding site as the MAO-B inhibitors. 9 , 10 Moreover, we have found that the PET tracers such as SL25.1188 11 also bind to the same substrate binding site. It is also speculated that when the substrate site is not available due to the binding of irreversible MAO-B inhibitors or because the ligand molecular volume is larger than the cavity volume then the entrance cavity is the preferred site for ligand binding.…”
Section: Introductionmentioning
confidence: 89%
“… 7 , 8 Recent studies by an author of this article also demonstrated that the tau PET tracers also target the same binding site as the MAO-B inhibitors. 9 , 10 Moreover, we have found that the PET tracers such as SL25.1188 11 also bind to the same substrate binding site. It is also speculated that when the substrate site is not available due to the binding of irreversible MAO-B inhibitors or because the ligand molecular volume is larger than the cavity volume then the entrance cavity is the preferred site for ligand binding.…”
Section: Introductionmentioning
confidence: 89%
“…Although MAO inhibitors are valuable therapeutic agents for disorders such as Parkinson’s disease, they are not candidates for specific dopaminergic imaging agents due to this widespread distribution. Nevertheless, they are an important component of the dopamine system, and have been the target for in vivo PET radiotracer development [ 68 , 69 ]. There have been three approaches to MAO radioligands for PET: suicide inhibitors, reversible antagonists, and metabolic substrates.…”
Section: Monoamine Oxidases (Mao): Inhibitors and Substratesmentioning
confidence: 99%
“…For this approach, radiotracers were selected or designed to be BBB permeable and subject to metabolism by MAO in brain tissues, with the resultant radiolabeled metabolites irreversibly trapped in the tissues in proportion to the enzymatic activity. None of these potential MAO radiotracers have yet been taken to human studies, but they might provide a different measure of MAO enzymatic activities than the radiolabeled enzyme inhibitors [ 69 ].…”
Section: Monoamine Oxidases (Mao): Inhibitors and Substratesmentioning
confidence: 99%
“…These radiotracers have been employed to monitor NET availability in different related diseases, including obesity, major depressive disorder, and Parkinson’s disease. Likewise, radiotracers, for instance, [ 11 C]Harmine demonstrated clinical success for in vivo brain imaging of MAO-A, respectively [ 55 , 56 , 57 ]. [ 11 C]Harmine has been applied in several-PET neuroimaging studies to study the role of MAO-A in different pathological conditions, including nicotine/alcohol dependence, and Alzheimer’s disease.…”
Section: Introductionmentioning
confidence: 99%